Development of an Enzyme-Linked Immunosorbent Assay Based on a Monoclonal Antibody for the Rapid Detection of Citrinin in Wine - Xingdong Yang; Yang Qu; Chenchen Wang; Lihua Wu; Xiaofei Hu (Foods)
The ingestion of food contaminated with citrinin (CIT) poses a variety of health risks to humans and animals. The immunogens (CIT-COOH-BSA, CIT-H-BSA) and detection antigen (CIT-COOH-OVA, CIT-H-OVA) were synthesised using the active ester method (-COOH) and formaldehyde addition method (-H). A hybridoma cell line (3G5) that secretes anti-CIT monoclonal antibodies (mAbs) was screened via CIT-H-BSA immunisation of mice, cell fusion, and ELISA screening technology. The cell line was injected intraperitoneally to prepare ascites. The reaction conditions for the indirect competitive ELISA (ic-ELISA) were optimised, and an ic-ELISA method for detecting CIT was preliminarily established. The results revealed that the IC50 of CIT from optimised ic-ELISA was 37 pg/mL, the linear detection range was 5.9~230 pg/mL, and the cross-reaction (CR) rate with other analogues was less than 0.01%. The intra-assay and interassay sample recovery rates of CIT were 84.7~92.0% and 83.6~91.6%, and the coefficients of variation (CVs) were less than 10%. The ic-ELISA of CIT established in this study was not significantly different from the HPLC results and is rapid, highly sensitive and strongly specific, providing technical support for the detection of CIT.